The election of the president of the republic under the 2020 Constitutional Amendments and Organic Law No. 21-01 on elections - Boutbig, Fateh (The International tax journal, 2025)
The presidential election in Algeria represents a fundamental pillar of the political system and a decisive mechanism for the peaceful transfer of power. However, the evolution of Algeria’s constitutional framework, particularly following the 2020 Constitutional Amendments and the promulgation of Organic Law No. 21-01 on the Electoral System, has introduced profound transformations in the organisation, regulation, and conduct of presidential elections. This study begins from the premise that understanding these reforms requires a comprehensive legal analysis of the principles, mechanisms, and conditions that govern the candidacy and electoral campaign process. The research examines the extent to which the new provisions have redefined the eligibility criteria, transparency guarantees, and institutional oversight intended to ensure fairness and legitimacy in the electoral process. It also analyses the relationship between the constitutional principles and the implementing legislative instruments, as reflected in the Official Journal of the People’s Democratic Republic of Algeria, to assess the degree of harmony between theory and practice. Furthermore, the study discusses the legal and political implications of these reforms on democratic consolidation, focusing on how the revised system balances the demands of political stability with the aspirations for genuine representation and public participation.